Functional Conservation of Divergent p63-Bound cis-Regulatory Elements - Gallardo-Fuentes, Lourdes; Santos-Pereira, José M.; Tena, Juan J. (Frontiers in Genetics, 2020)
The transcription factor p63 is an essential regulator of vertebrate ectoderm development, including epidermis, limbs, and craniofacial tissues. Here, we have investigated the evolutionary conservation of p63 binding sites between zebrafish and human. First, we have analyzed sequence conservation of p63 binding sites by comparing ChIP-seq data from human keratinocytes and zebrafish embryos, observing a very poor conservation. Next, we compared the gene regulatory network orchestrated by p63 in both species and found a high overlap between them, suggesting a high degree of functional conservation during evolution despite sequence divergence and the large evolutionary distance. Finally, we used transgenic reporter assays in zebrafish embryos to functionally validate a set of equivalent p63 binding sites from zebrafish and human located close to genes involved in epidermal development. Reporter expression was driven by human and zebrafish binding sites to many common tissues related to p63 expression domains. Therefore, we conclude that the gene regulatory network controlled by p63 is highly conserved across vertebrates despite the fact that p63-bound regulatory elements show high divergence.